2001
DOI: 10.1046/j.0269-283x.2001.00317.x
|View full text |Cite
|
Sign up to set email alerts
|

Tick‐borne encephalitis virus in northern Italy: molecular analysis, relationships with density and seasonal dynamics of Ixodes ricinus

Abstract: Ixodes ricinus ticks were collected from dragging vegetation and from shot roe deer in the province of Trento and Belluno in northern Italy. Ticks were pooled for analyses and from 1060 pools of ticks collected in the province of Belluno and 12390 tick samples collected in Trentino, four proved positive by immunofluorescence microscopy using a tick-borne encephalitis (TBE)-specific antiserum. The identity of the virus isolates was determined by RT-PCR cycle sequencing and they were all found to be closely simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
45
1
4

Year Published

2003
2003
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 22 publications
7
45
1
4
Order By: Relevance
“…The Bayesian phylogenetic analyses provide results that are consistent with those of previous studies, indicating that the new Italian TBEV sequences generated here belong to the European TBEV subtype (Hudson et al, 2001;D'Agaro et al, 2009). Interestingly, we found a substantial amount of genetic divergence between these Italian TBEV sequences, despite both the relatively short E gene sequence fragments analysed and the restricted geographical range (Trento province only).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The Bayesian phylogenetic analyses provide results that are consistent with those of previous studies, indicating that the new Italian TBEV sequences generated here belong to the European TBEV subtype (Hudson et al, 2001;D'Agaro et al, 2009). Interestingly, we found a substantial amount of genetic divergence between these Italian TBEV sequences, despite both the relatively short E gene sequence fragments analysed and the restricted geographical range (Trento province only).…”
Section: Discussionsupporting
confidence: 80%
“…Interestingly, we found a substantial amount of genetic divergence between these Italian TBEV sequences, despite both the relatively short E gene sequence fragments analysed and the restricted geographical range (Trento province only). Comparison of the sequences at the nucleotide and amino acid levels showed that this variability is mostly caused by synonymous substitutions, as observed previously by Hudson et al (2001). In particular, we found that, whilst six synonymous substitutions separate the two Italian sequences, only one nonsynonymous substitution was observed, at aa 513, where ITTN 2006 6-7 has a glutamine and ITTN 2006 12-8 has a lysine (see Table 1).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Our study was carried out at the Southern edge of the TBE virus distribution, in an isolated TBE focus (Hudson et al, 2001). The area is located in Valle dei Laghi, Trentino (grid reference, 1652050E 5093750N) in the north-eastern Italian Alps.…”
Section: Study Areamentioning
confidence: 99%
“…In the Scottish uplands, the complexity of the system is illustrated by the wide range of tick hosts including sheep (Ovis aries L), red deer (Cervus elaphus L), mountain hare (Lepus timidus L) and red grouse (Lagopus lagopus scoticus L) (Gray et al 1992;Hudson et al 1997;Hudson et al 2001;Laurenson et al 2003). Of particular interest is the impact that the sheep tick may have on red grouse, an economically important gamebird, which has been in long term decline (Shaw et al 2004).…”
Section: Introductionmentioning
confidence: 99%